Unveiling the security concerns of low carbon development: climate security analysis of the undesirable and unintended effects of mitigation and adaptation. (7th February 2020) - Mirumachi, Naho; Sawas, Amiera; Workman, Mark
ABSTRACT: In debates of climate action, low carbon development has been widely advocated as an opportunity arising from climate change. This paper problematizes low carbon development, arguing that there are undesirable, unintended or perverse effects that give rise to distinct and serious security concerns. The literature on climate security has addressed the effects of climate threats on conflict but there is a notable paucity of research analysing the security implications of responses to climate change in the form of low carbon development. The paper presents critical analysis of the ways low carbon development yields new security concerns as well as entrenching existing ones. Five dimensions of security are examined: spatially uneven effects of low carbon development; violent imaginaries of the global south and the production of 'ungoverned spaces'; non-violent yet harmful instances of conflict; marginalization and dispossession; depoliticized, techno-managerial effects of resilience. The paper shows that climate (in)security manifests in variegated ways between different populations and spatial scales. Consequently, how, when for whom low carbon development becomes a threat or opportunity is socially constructed and deeply political.